Racial Threat and Opposition to the Re-Enfranchisement of Ex-Felons - Chiricos, Ted; Padgett, Kathy; Bratton, Jake; Pickett, Justin T.; Gertz, Marc (International Journal of Criminology and Sociology, 2012)
Prior research demonstrates that racial threat is related to the time, place and severity of disenfranchisement laws for ex-felons. This study builds on that work by examining whether perceived racial threat helps to account for public opposition to the abolition of disenfranchisement policies. To do this, we draw on interview data from a survey of 1,575 Florida adults randomly sampled in 2005. Perceived racial composition of neighborhood and the perceived involvement of blacks in several crimes – the racial typification of crime – are our measures of perceived racial threat. Perceived racial composition is unrelated to opposition to re-enfranchisement of ex-felons. But the racial typification of crime significantly predicts that opposition, independent of the effects of general punitiveness, conservatism, and other predictors. Among white respondents that relationship is strongest for those who are liberal/moderate and generally less punitive and is not effected by varying levels of racial threat measured at macro-social levels.